Perlindungan Hukum Atas Display Produk Mendekati Kedaluwarsa di Tempat Diskon - Sinaga, Roulinta Yesvery; Sihite, Sri Rumada (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: Displaying near-expiration products at discount stores is a common practice. While this practice is not explicitly prohibited by law, it needs to be considered in terms of health and consumer rights.Purposes of the Research: To examine the impacts and implications of displaying products nearing expiration at discount stores and to assess the legal protection and responsibility regarding such product displays.Methods of the Research: The research method used is normative juridical with legal, conceptual, and case approaches.Results of the Research: The practice of displaying near-expiration products at discount stores can have negative impacts on consumers and businesses. Legal protection for this practice consists of preventive measures through collaboration between relevant parties, periodic checks, discount product labeling, consumer awareness, and supervision by relevant institutions. Responsive legal protection can be pursued through litigation or non-litigation routes. The responsibility of businesses for this practice should be carefully reviewed, as they may become involved in legal conflicts and cause both material and immaterial losses to consumers. Fault-based liability should ideally be applied, but consumers need to make efforts and critically gather evidence, outline losses, and describe the causality of negative effects from purchasing display products.